Regulation of platelet plug formation by phosphoinositide metabolism - Min, Sang H. (American Society of Hematology, 2013)
Phosphatidylinositol and its phosphorylated derivatives, phosphoinositides, are minor constituents of phospholipids at the cellular membrane level. Nevertheless, phosphatidylinositol and phosphoinositides represent essential components of intracellular signaling that regulate diverse cellular processes, including platelet plug formation. Accumulating evidence indicates that the metabolism of phosphoinositides is temporally and spatially modulated by the opposing effects of specific phosphoinositide-metabolizing enzymes, including lipid kinases, lipid phosphatases, and phospholipases. Each of these enzymes generates a selective phosphoinositide or second messenger within precise cellular compartments. Intriguingly, phosphoinositide-metabolizing enzymes exist in different isoforms, which all produce the same phosphoinositide products. Recent studies using isoform-specific mouse models and chemical inhibitors have elucidated that the different isoforms of phosphoinositide-metabolizing enzymes have nonredundant functions and provide an additional layer of complexity to the temporo-spatial organization of intracellular signaling events. In this review, we will discuss recent advances in our understanding of phosphoinositide organization during platelet activation.